Immune responses at brain barriers and implications for brain development and neurological function in later life - Stolp, Helen B.; Liddelow, Shane A.; Sá-Pereira, Inês; Dziegielewska, Katarzyna M.; Saunders, Norman R. (Frontiers in Integrative Neuroscience, 2013)
For a long time the brain has been considered an immune-privileged site due to a muted inflammatory response and the presence of protective brain barriers. It is now recognised that neuroinflammation may play an important role in almost all neurological disorders and that the brain barriers may be contributing through either normal immune signalling, or disruption of their basic physiological mechanisms. The distinction between normal function and dysfunction at the barriers is difficult to dissect, partly due to a lack of understanding of normal barrier function and partly because of physiological changes that occur as part of normal development and ageing. Brain barriers consist of a number of interacting structural and physiological elements including tight junctions between adjacent barrier cells and an array of influx and efflux transporters. Despite these protective mechanisms, the capacity for immune-surveillance of the brain is maintained, and there is evidence of inflammatory signalling at the brain barriers that may be an important part of the body’s response to damage or infection. This signalling system appears to change both with normal ageing, and during disease. Changes may affect diapedesis of immune cells and active molecular transfer, or cause rearrangement of the tight junctions and an increase in passive permeability across barrier interfaces. Here we review the many elements that contribute to brain barrier functions and how they respond to inflammation, particularly during development and aging. The implications of inflammation–induced barrier dysfunction for brain development and subsequent neurological function are also discussed.